PENGEMBANGAN SISTEM DESTILASI MINYAK ATSIRI BERBASIS IOT UNTUK PEMBERDAYAAN PETANI DI DESA CIBODAS - Mulia, Sandy Bhawana; Sunarya, Adhitya Sumardi; Lilansa, Noval; Budiyarto, Aris; Suryatini, Fitria; Rokhim, Ismail; Pratama, Rizqi Aji (Universitas Padjadjaran, 2026)
Cibodas Village, located in Lembang District, West Bandung Regency, has significant potential for essential oil production due to its abundant natural resources. However, the main challenge lies in the limited technology available, resulting in low quality and quantity of essential oil production. To address this issue, an Internet of Things (IoT)-based essential oil distillation system was developed as an effort to empower local farmers. This study encompasses the design, development, and testing of an essential oil distillation system that utilizes digital technology for real-time process monitoring and control. Experimental testing using lemongrass as the raw material produced high-quality essential oil, with a yield of 0.28 liters from 35 kilograms of raw material during a 4-hour distillation process under a controlled temperature of 80°C. Furthermore, the outreach and training activities conducted for local farmers yielded positive outcomes, as reflected in their strong enthusiasm for adopting this new technology. This innovation is expected to sustainably enhance productivity, efficiency, and the economic value of agricultural products in Cibodas Village.Desa Cibodas Kecamatan Lembang Kabupaten Bandung Barat memiliki potensi besar untuk memproduksi minyak atsiri karena ketersediaan sumber daya alam yang melimpah. Namun, tantangan utama adalah keterbatasan teknologi yang mengakibatkan rendahnya kualitas dan kuantitas produksi minyak atsiri. Untuk mengatasi permasalahan ini, telah dikembangkan sistem destilasi minyak atsiri berbasis Internet of Things (IoT) sebagai upaya pemberdayaan petani lokal. Penelitian ini mencakup perancangan, pembangunan, dan pengujian sistem destilasi minyak atsiri dengan memanfaatkan teknologi digital untuk monitoring dan kontrol proses. Pengujian menggunakan bahan baku tanaman serai menghasilkan minyak atsiri berkualitas dengan rendemen 0,28 liter dari 35 kg bahan untuk pengujian selama 4 jam untuk suhu terkontrolasi pada besaran 80o C. Selain itu, kegiatan penyuluhan kepada petani setempat menunjukkan hasil yang positif, dengan antusiasme tinggi terhadap teknologi baru ini. Inovasi ini diharapkan dapat meningkatkan produktivitas, efisiensi, dan nilai ekonomi hasil panen petani Desa Cibodas secara berkelanjutan.